Podocalyxin, Isthmin-1, and Pentraxin-3 Immunoreactivities as Emerging Immunohistochemical Markers of Fibrosis in Chronic Hepatitis B - Ozguler, Muge; Hancer, Serhat; Solmaz, Ozgen Arslan; Kuloglu, Tuncay (Mdpi, 2025)
Introduction and Objectives: Persistent hepatic inflammation serves as a key driver of fibrogenesis in chronic hepatitis B. Fibrosis is a complex molecular and cellular process. Podocalyxin is a type I transmembrane sialomucin, and physiological expression of podocalyxin has been identified in the liver. Pentraxin 3 plays a crucial role in humoral innate immune responses. Isthmin-1 has been associated with metabolic regulation and immune response modulation. We aimed to evaluate the immunoreactivities of podocalyxin, Isthmin-1, and pentraxin-3 in the liver tissue of patients with chronic hepatitis B. Materials and Methods: Power analysis was performed (effect size (f = 0.5), (alpha) = 0.05 and statistical power of 0.80). Sample size was calculated to be a total of 63 samples, with 21 samples per group. Individuals with negative hepatitis serology and normal liver histopathology, from whom liver tissue was obtained for any reason, were designated as the control group. Liver specimens of chronic hepatitis B were categorized into F0-F2 (no or mild fibrosis) and >= F3 (advanced fibrosis). Immunohistochemical staining was performed to assess the expression and immunoreactivity of Podocalyxin, Isthmin-1, and Pentraxin-3. A histoscore was created based on the prevalence of staining immunoreactivity (0.1: <25%, 0.4: 26-50%, 0.6: 51-75%, 0.9: 76-100%) and intensity (0: none, +0.5: very low, +1: low, +2: moderate, +3: severe). Results: A statistically significant increase in Podocalyxin, Pentraxin-3, and Isthmin-1 immunoreactivities was found in fibrotic liver tissue compared to normal liver tissue and mild fibrotic groups (p < 0.05). Conclusions: We concluded that our findings suggest these proteins may have an additional role in the progression of liver fibrosis in chronic hepatitis B.
Keywords: chronic hepatitis B; liver fibrosis; Podocalyxin; Pentraxin-3; Isthmin-1